How Do Firms Respond to Parental Leave Absences? - Anne Ardila Brenøe; Urša Krenk; Andreas Steinhauer; Josef Zweimüller (Institute of Labor Economics (IZA), 2025)
How do firms adjust their labor demand when a female employee takes temporary leave after childbirth? Using Austrian administrative data, we compare firms with and without a birth event and exploit policy reforms that significantly altered leave durations. We find that (i) firms adjust hiring, employment, and wages around leave periods, but these effects fade quickly; (ii) adjustments differ sharply by gender, reflecting strong gender segregation within firms; (iii) longer leave entitlements extend actual leave absences but have only short-term effects; and (iv) there is no impact on firm closure up to five years after birth.
Keywords: H2; H5; J2; J08; J13; 330; absence duration; gender; labor demand; labor supply; firms; family leave